Digital storytelling in online elementary science education: a case study on science and technology club activities - Korukluoglu, Pinar; Yucel-Toy, Banu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
With the spread of online education due to the COVID-19 pandemic, instructional technologies have gained importance. One of these applications is digital story, which is the presentation of a story specific to a particular subject using various digital multimedia such as visual, audio and video. This case study aimed to reveal the effect of the digital story-based Science and Technology Club on students' digital story performance and academic achievement in the science course and to examine the students' and teacher's reflections on digital story-based experiences. As data sources, interviews with 16 students, teacher's reflection notes, students' digital stories and students' science course grades were analyzed. The evaluation of digital stories showed that they performed best in providing relevance of the content to science but had problems integrating voiceover and music. The students' science course grades significantly increased. The results also revealedthat digital story-based activities encouraged them to research and learn new information and their audio-visual features facilitated their learning. Moreover, students expressed that the use of digital stories triggered their technology skills and improved their social skills. Despite its contributing and motivating features, they stated various difficulties because of spending a lot of time in front of the screen while using this application.
Keywords: Science education; digital storytelling; learning technologies; online education; LEARNING-MOTIVATION; Education & Educational Research